Sculpting the future of medical data visualization - Harris, Justus (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Art beyond its aesthetics can create empathy and understanding of the effects of illness, whether chronic like diabetes or triggered by environmental pollution such as water contamination. Utilizing the sense of touch, sight, and sound as a dynamic method of storytelling art can communicate where traditional spoken word and data representation fall short. For me the often invisible fluctuations of my blood glucose I experience as someone living with type 1 diabetes can be visualized and shared through “Diabetes Data Sculptures” (Figure 1). These sculptures take the thousands of blood glucose readings and other variables that I collect each month and consolidate them into color coded and tactile summaries of that data (Figure 2).